2017
DOI: 10.1080/17453674.2017.1281058
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors and their soluble forms differ in the knee and thumb basal osteoarthritic joints

Abstract: Background and purposeAlthough the pathogenesis of osteoarthritis (OA) is not well understood, chondrocyte-mediated inflammatory responses (triggered by the activation of innate immune receptors by damage-associated molecules) are thought to be involved. We examined the relationship between Toll-like receptors (TLRs) and OA in cartilage from 2 joints differing in size and mechanical loading: the first carpometacarpal (CMC-I) and the knee.Patients and methodsSamples of human cartilage obtained from OA CMC-I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Soluble forms of TLR2 have been detected in human fluids such as breast milk, amniotic fluid, saliva [ 86 , 87 ], and in synovial fluid of human joints with osteoarthritis [ 88 ]. Intestinal epithelial cells also produce sTLR2.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Soluble forms of TLR2 have been detected in human fluids such as breast milk, amniotic fluid, saliva [ 86 , 87 ], and in synovial fluid of human joints with osteoarthritis [ 88 ]. Intestinal epithelial cells also produce sTLR2.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…To date, four extracellular sTLRs have been identified in humans, including sTLR-1, sTLR-2, sTLR-4, and sTLR-6. Of these four extracellular sTLRs, sTLR-2 and sTLR-4 have been detected in most body fluids including saliva, serum, urine and breast milk (57).…”
Section: Discussionmentioning
confidence: 99%
“…To date thirteen mammalian TLRs and many of their ligands have been identified. In addition to membrane-associated TLRs, soluble forms of TLRs (sTRLs) have been identified in serum, urine, tears and saliva (57). sTLRs are thought to act as negative regulators and inhibit TLR mediated signaling_pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, functional studies have demonstrated that primary FLS from healthy and OA patients express TLRs, which actively respond to several DAMP ligands, such as tenascin-C or S100A8/A9 [20,21]. In the OA synovial fluid TLR4 is also present in the soluble form, and it is associated with the OA severity, making sTLR4 an intriguing biomarker [22,23]. TLRs activation and the ensuing NF-kB activation is followed by the production of chemokines (e.g., IL-8 and CCL5) and cytokines (e.g., IL-1, IL-6, and TNF) which participate in the recruitment of macrophages, granulocytes, and lymphocytes cell into the synovium of OA patients [24].…”
Section: Tlrs In Osteoarthritismentioning
confidence: 99%
“…All TLRs are present in articular cartilage and are known to be upregulated in OA cartilage, particularly in the lower limbs such as knee and hip cartilage [38]. However, a recent study indicated that there are also joint-specific TLR expression patterns, particularly between hand and knee OA, which might also implicate differential immune mechanisms of large and small joints in OA [23].…”
Section: Tlrs and Chondrocytesmentioning
confidence: 99%